Kepentingan Korban vs Kepentingan Hukum: Implementasi Penanganan Kasus Kekerasan Seksual di Perguruan Tinggi - andini, oringustaandini (Legislatif, 2023)
This study aims to describe the obstacles in handling sexual violence cases in universities, namely the reluctance of victims to report cases of sexual violence to law enforcement officials. This research uses normative research methods with basic approach and statutory approach. The Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 30 year 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education and Law 12 Number year 2022 Sexual Violence Criminal Acts doesn’t necessarily make victims free from fear over their reporting even it’s a legal interest as well as a mandate of the TPKS law, the reluctance of victims to take legal action for the sake of mental health is the choice and interest of victims. This situation makes the legal interests and the interests of the victim face each other and has the potential to make the perpetrator of sexual violence report the victim for the report he submitted to the sexual violence companion under the pretext of defamation or defamation crimes. This article recommends that in carrying out their duties, sexual violence assistants can better interpret the best interests of victims so that victims of sexual violence in handling them are also given legal education in the hope of increasing legal awareness of legal interests, but if the victims are still reluctant to report because psychological impact, it can be ruled out because the best interests of the victim are the thing that must come first.